Prevalence and patterns of dyslipidaemia among adult Sri Lankans - Herath, H. R. I. S.; Katulanda, P.; Matthews, D. R.; Sheriff, M.H.R.; Constantine, G. R.; De Vas Gunawardena, A. N. P.; Katulanda, G.W. (My University, 2010)
Cardiovascular disease (CVD) remains the leading cause of death in Sri Lanka. Dyslipidaemia is a major risk factor for development of CVD. Sri Lanka has no countrywide data on prevalence and patterns of dyslipidaemia. We aimed to determine the age and sex specific distribution and patterns of dyslipidaemia among adults in Sri Lanka. Methods: Sri Lanka diabetes and cardiovascular study is a cross sectional study carried out in 2005 - 2006 period. We selected a nationally representative sample of 5000 subjects over 18 years by a multistage random cluster sampling technique. Data were collected using an interview, physical examination and analysis of a 12-hour fasting blood sample. We measured total cholesterol (TC), high density lipoprotein cholesterol (HDLC) and triglycerides (TG). Low density lipoprotein cholesterol (LDLC) and TC/HDLC were calculated. Results: The means (SD) of TC, HDLC, LDLC and TG were 5.35(1.13),1.21(0.28),3.51(0.97),1.38 (0.75), mmol/l. The median (IQR) TC/HDLC was 4.49 (3.75-5.29). Women had significantly higher TC, HDLC and LDLC while men had significantly higher TG and TC/HDLC. The mean TC, HDLC, LDLC, TG and median TC/HDLC increased significantly with increased age. The prevalence of hypercholesterolaemia (>5.2 mmoI/L), high LDLC (>3.4mmol/L), low HDLC O(
Sri Lanka Medical Association - 123rd Annual Scientific Sessions: 2010; 15p.